Beyond dermatomes disseminated Herpes zoster in the immunocompetent: two rare cases - Devaraj, Yogesh; Govindaraju, Namratha; Panigrahi, Shubhashree; Johnson, Richin Anna (International Journal of Research in Dermatology, 2024)
Herpes zoster is typically a localized reactivation of the varicella-zoster virus (VZV) that occurs in individuals following a primary varicella infection (chickenpox). Disseminated herpes zoster, characterized by widespread vesicular lesions beyond the primary dermatome, is uncommon and usually associated with immunocompromised states. Till date only 25 immunocompetent patients with disseminated HZ have been reported in literature. We report two such cases of disseminated HZ in immunocompetent individuals. The 1st patient is a 53-year-old woman with painful, itchy multiple grouped erythematous papules, vesicles, and bullae over right T8-T9 dermatome and multiple papules, crusted papules, and vesicles over face associated with fever and fatigue. The 2nd patient is an 8-year-old boy with multiple grouped clear vesicles and bullae with erythematous base involving the left S1-S5 dermatome. Multiple discrete erythematous papules and vesicles (active and crusted) were noted over trunk, right forearm, left arm, bilateral thigh and left mandibular area. Routine laboratory investigations were within normal limits. Tzanck smears were done, and multinucleated giant cells were seen in both cases. They were treated with antivirals and showed improvement. We have reported these two cases of disseminated HZ due to their occurrence in immunocompetent patients, which is a very rare phenomenon.